2014
DOI: 10.2478/s11536-013-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of cholelithiasis in female patients with metabolic syndrome

Abstract: AbstractCholesterol gallstone disease is often associated with the metabolic syndrome. Female gender is an unmodifiable risk factor for cholelithiasis and, in its turn, the metabolic syndrome features a sexual dimorphism which warns that a global approach might overlook important discrimination. We carried out a retrospective analytical case-control study in order to perform a comparative analysis between two groups of female patients with metabolic syndrome and gallstones (n=6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In terms of direct bilirubin, also normal mean Although there is no parallel relationship with blood lipids level, increased lipid components excretion through bile directly promote the formation of cholesterol stones. Total cholesterol, direct bilirubin and especially lean body weight might provide simple stratification tools for obese women, outlining a high risk profile for developing gallstones [43].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of direct bilirubin, also normal mean Although there is no parallel relationship with blood lipids level, increased lipid components excretion through bile directly promote the formation of cholesterol stones. Total cholesterol, direct bilirubin and especially lean body weight might provide simple stratification tools for obese women, outlining a high risk profile for developing gallstones [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no parallel relationship with blood lipids level, increased lipid components excretion through bile directly promote the formation of cholesterol stones. Total cholesterol, direct bilirubin and especially lean body weight might provide simple strati cation tools for obese women, outlining a high risk pro le for developing gallstones [43].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, this disorder occurs asymptomatically, and only 20% of people with cholelithiasis experience pain and complications. The most common risk factor of cholelithiasis is gender, with females being one of the unmodifiable risk factors and is also related to metabolic syndrome events [4]. Pimpale et al [5] stated that cholelithiasis is commonly found in females in the 4 th to 5 th decade of life, with abdominal pain being the most typical symptom.…”
Section: Introductionmentioning
confidence: 99%